2021
DOI: 10.1016/j.hpb.2020.11.598
|View full text |Cite
|
Sign up to set email alerts
|

Roundabout homolog 1 inhibits proliferation via the YY1-ROBO1-CCNA2-CDK2 axis in human pancreatic cancer

Abstract: Abundant stroma of pancreatic ductal adenocarcinoma (PDAC) produces various microenvironmental < niche> factors. PDAC organoids have different dependencies on niche factors; while there are PDAC subtypes independent of niche factors as represented by conventional pancreatic cancer cell lines, there are also PDAC subtypes that strongly depend on niche factors. We performed the PDAC subtype classification based on niche dependency and their morphological phenotypes and investigated the correlation between niche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…CCNA2 could also act as a significant downstream facilitating tumor progression. Chen et al suggested that ROBO1 could promote the development of pancreatic cancer via CCNA2/CDK axis [36]. Interestingly, our study illustrated that CCNA2 could enhance the development of ccRCC via several immunerelated signals, including immunodeficiency, natural killer cell-mediated cytotoxicity pathway, and IL6-JAK-STAT3 pathways.…”
Section: Discussionsupporting
confidence: 48%
“…CCNA2 could also act as a significant downstream facilitating tumor progression. Chen et al suggested that ROBO1 could promote the development of pancreatic cancer via CCNA2/CDK axis [36]. Interestingly, our study illustrated that CCNA2 could enhance the development of ccRCC via several immunerelated signals, including immunodeficiency, natural killer cell-mediated cytotoxicity pathway, and IL6-JAK-STAT3 pathways.…”
Section: Discussionsupporting
confidence: 48%
“…While an unregulated level of ROBO1 expression in PC tumor stroma was found to support tumor invasiveness and metastasis [36], ROBO1 overexpression in PC cells (PANC-1 and MiaPaca-2) was found to reduce cell proliferation, suggesting a tumor suppressive effect [37]. Our data for HUVECs containing exosomal miR-29b showed ROBO1 overexpression could rescue a decrease in VEGF expression, as well as decreases in cell migration and tube formation after miR-29b mimic transfection.…”
Section: Discussionmentioning
confidence: 63%